2017
DOI: 10.1111/jace.14668
|View full text |Cite
|
Sign up to set email alerts
|

Structural and emission properties of Eu3+‐doped alkaline earth zinc‐phosphate glasses for white LED applications

Abstract: Quaternary alkaline earth zinc-phosphate glasses in molar composition (40 À x) ZnO -35P 2 O 5 -20RO -5TiO 2 -xEu 2 O 3 (where x=1 and R=Mg, Ca, Sr, and Ba) were prepared by melt quenching technique. These glasses were studied with respect to their thermal, structural, and photoluminescent properties. The maximum value of the glass transition temperature (T g ) was observed for BaO network modifier mixed glass and minimum was observed for MgO network modifier glass. All the glasses were found to be amorphous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 44 publications
5
18
0
4
Order By: Relevance
“…The increase of T g may due to the higher eld strength cations (O 2À > F À ) create a more tightly bonded glass structure with SnO replacing SnF 2 in these glasses. 19 Although the temperature increased, the maximum T g is below 200 C, which meets the requirements of low-temperature sealing glasses.…”
Section: Xrd and T Gmentioning
confidence: 82%
“…The increase of T g may due to the higher eld strength cations (O 2À > F À ) create a more tightly bonded glass structure with SnO replacing SnF 2 in these glasses. 19 Although the temperature increased, the maximum T g is below 200 C, which meets the requirements of low-temperature sealing glasses.…”
Section: Xrd and T Gmentioning
confidence: 82%
“…The decay curves were fitted with different exponential equations. It can be observed that all the decay curves were best fitted biexponentially with the following equation as shown in Figure :It=I0+A1exp-tτ1+A2exp-tτ2where It and I0 signify the luminescence intensities at time t and 0, respectively. A 1 and A 2 are fitting constant.…”
Section: Resultsmentioning
confidence: 99%
“…TeO 2 glasses can be classified into either Te‐rich glasses with around 50 mol% TeO 2 in binary and ternary systems with application in lasers, optical fibers, amplifiers, 1‐11 or into low‐Te glasses where TeO 2 is only added in low amounts as dopant 3,12‐15 . TeO 2 glasses are promising low phonon hosts for rare‐earth elements 1,16‐23 or present luminescence properties themselves 2 . Having a broadband NIR emission and a lifetime of tens of microseconds, Te glasses of different compositions (zinc oxide, phosphate, vanadate, borate, etc) may be promising material for fabricating broadband optical fibers, amplifiers, windows, lenses or tunable lasers in visible (Vis) 3‐10,24‐27 or in infrared (IR) domain 11,24,28 …”
Section: Introductionmentioning
confidence: 99%